A comprehensive assessment on material, exergy and emission networks for the integrated iron and steel industry. (15th November 2021) - Sun, Jingchao; Na, Hongming; Yan, Tianyi; Qiu, Ziyang; Yuan, Yuxing; He, Jianfei; Li, Yingnan; Wang, Yisong; Du, Tao
Abstract: Intensive energy consumption and high pollutant emission have always been the obstacles for achieving the sustainable development of the iron and steel (I&S) industry. The complex material flows, energy flows and emission flow of I&S industry require better assessment to implement comprehensive governance and impact analysis. The 48-month data of a typical I&S enterprise is used for evaluating intensities and analyzing influencing factors from the perspective of material, exergy and emission networks. The results show that the exergy intensity and carbon emission intensity of the whole site including main processes and auxiliary processes are 23.804 GJ/t-CS and 1642.7 kg/t-CS, respectively. In particular, auxiliary process plays a critical role, whose exergy loss accounts for about 28.85% of the total. The terms of energy structure, technology capacity, product structure and environmental conditions are considered to analyze on the influencing factors of the case, and then providing relevant suggestions. On the whole, integration assessment of material-exergy-emission networks of I&S industry is necessary and helpful to find their changes and migration, and to further implement energy management and emission reduction. Highlights: Material-exergy-emission network is analyzed for the whole iron & steel enterprise. The data of main and auxiliary processes with time granularity are analyzed. The intensities of energy, exergy and emission of various products are presented. The influencing factors for the material-exergy-emission network are discussed.